CTA Spot Sign Predicts Hematoma Expansion in Patients with Delayed Presentation After Intracerebral Hemorrhage - Brouwers, H. Bart (2012)
BACKGROUND: Hematoma expansion after acute intracerebral hemorrhage occurs most frequently in patients presenting within 3 h of symptom onset. However, the majority of patients present outside this window or with an unknown onset time. We investigated the prevalence of hematoma expansion in these patients and assessed the accuracy of the CT angiography (CTA) spot sign for identifying risk of hematoma expansion. METHODS: We analyzed 391 consecutive patients undergoing CTA and a followup CT. CTA spot sign readings were performed by two experienced readers and hematoma expansion was assessed by means of semi-automated software. RESULTS: Hematoma expansion occurred in 18 % of patients. When stratified by time from symptom onset to initial CT, hematoma expansion rates were: 39 % within 3 h; 11 % between 3 and 6 h, 11 % beyond 6 h (but with known onset), and 20 % in patients with unknown symptom onset. Of patients who developed hematoma expansion, only 38 % presented within 3 h. The accuracy of the spot sign in predicting hematoma expansion was 0.67 for patients presenting within 3 h, 0.83 between 3 and 6 h, 0.88 after 6 h, and 0.76 for patients presenting with an unknown onset time. CONCLUSIONS: A substantial number of patients destined to suffer from hematoma expansion present either late or with an unknown symptom onset time. The CTA spot sign accurately identifies patients destined to expand regardless of time from symptom onset, and may therefore open a path to offer clinical trials and novel therapies to the many patients who do not present acutely.